A rare cause of anaemia in multiple myeloma - Kalidindi, Lakshmipriya; Kalapan, Mahendra Kumar; Bathena, Arunkumar; Mohanan, Jagadeesan (International Journal of Advances in Medicine, 2022)
Multiple myeloma is a neoplastic plasma cell dyscrasia. Anaemia in multiple myeloma is usually related to many factors, of which the commonest cause being anaemia of chronic disease. We reported a 67 years old hypertensive male presented with low back pain and loss of appetite. Investigations revealed severe anaemia and elevated total serum protein with albumin/globulin (A/G) reversal (1:4). Bone marrow aspiration revealed plasma cell dyscrasia. Skeletal survey evaluation showed multiple osteolytic lesions. Serum protein electrophoresis revealed M spike in gamma globulin region with immunofixation suggestive of IgG and kappa monoclonal gammopathy. He was diagnosed as a case of multiple myeloma.. On evaluating the cause of severe anaemia, interestingly various findings suggestive of Autoimmune hemolytic anaemia (AIHA) were found. Packed red blood cell transfusion along with steroids was done for correction of severe anaemia. Review of literature showed that only about 4% of AIHA patients had multiple myeloma. We reported a rare case of multiple myeloma who presented with AIHA.